Capital Structure, Global Contractions and financial Performance: Evidence from Private Firms - Rehman, Shafiq; Muhammad, Ali; Rukh, Lala (Journal of Business & Tourism, 2023)
History has seen severe global credit crisis in 2007-2009, which has raised many concerns. One of the serious concerns are the leverage, performance relationship and the role of financial crisis in the performance of the private firms. Therefore, this study aims to examine the leverage, performance relationship and the impact of financial crisis on performance of private firms. To achieve our goal, the study used fixed effects regression model. Data for the study is extracted from the FAME database UK, for the period of 2004-2009. The results reveal that leverage and financial crisis have negatively affected the performance of private firms. Size and growth have positive impact on performance of private firms, while tangible assets have negative impact on performance. Further analysis reveals that both small and large firms were exposed to financial crisis. The findings of the study documents variations in the supply of finance and credit which has serious implications on their growth and performance. The findings of the study thus has implications for policy makers and financial regulations in the country.